A Mixed Methods Study of Self-Efficacy, the Sources of Self-Efficacy, and Teaching Experience - Gale, Jessica; Alemdar, Meltem; Cappelli, Christopher; Morris, David (Frontiers in Education, 2021)
Although teaching self-efficacy is associated with many benefits for teachers and students, little is known about how teachers develop a sense of efficacy in the early years of their careers. Drawing on survey (N=179) and interview (N=10) data, this study investigates the sources of self-efficacy in a national sample of teachers who participated in the Noyce program. All teachers completed an online survey that included both the Teacher Sense of Efficacy Instrument and open-ended items prompting them to reflect on the sources of their self-efficacy. Ten teachers participated in semi-structured follow-up interviews. Enactive mastery experiences were the most common source of self-efficacy identified by teachers, followed by social persuasions and vicarious experiences. Physiological and affective states were identified infrequently and more often related to negative experiences that lowered self-efficacy than to positive experiences. Beginning teachers identified more negative enactive experiences than either Novice (2-3 years experiences) or Career teachers. In interviews, teachers described how the sources combined or interacted to influence their self-efficacy. Findings contribute to better understandings of the sources of self-efficacy with implications for how best to support teachers at different stages of their careers.